B‐cell lymphoma with Mott cell differentiation in a cat. (7th March 2016) - Kanehara, Tomomi; Matsui, Naoko; Murakami, Mami; Maruo, Kohji; Mori, Takashi; Hirata, Akihiro; Yanai, Tokuma; Sakai, Hiroki
Abstract: A 12‐year‐old, male castrated Domestic Shorthair cat was presented to Animal Medical Center of Gifu Univeristy with anorexia and vomiting. Physical examination revealed an enlarged left tonsil and right mandibular lymph node (approximately 2–3× the normal size), and a submucosal mass on the right side of the epiglottis (1.5 × 2.0 cm). On computed tomography images, an enlarged left tonsil, and enlarged right mandibular, right pharyngeal, and left and right cervical lymph nodes were observed. Cytologic examination of smears of tonsil and lymph nodes revealed numerous medium‐ to large‐sized neoplastic lymphoid cells, approximately half of which contained one or several light‐blue homogenous globoid cytoplasmic inclusions (5–10 μm), which stained magenta with periodic acid–Schiff (PAS) stain. Histopathologic examination of the left tonsil revealed diffuse proliferation of medium‐ to large‐sized neoplastic lymphoid cells effacing the original lymphoid architecture. Half of the cells contained one or several eosinophilic globoid cytoplasmic inclusions, which stained magenta with PAS and showed positive immunohistochemical reactions for immunoglobulin M (IgM) and λ light chain. Neoplastic lymphoid cells were also CD20 +, Pax5 +, and MUM1 +, and CD3 − . Thus, the neoplastic lymphoid cells expressed a B‐cell immunophenotype, and the globoid cytoplasmic inclusions represented an aberrant IgM λ light chain accumulation, similar to Russell bodies. B‐cell lymphoma with Mott cell differentiation was diagnosed based on cytologic, histopathologic, and immunohistochemical features. This is the first report of B‐cell lymphoma with Mott cell differentiation in a cat.